Case Processing in the Development of Expertise in Life Sciences-What Can Eye Movements Reveal? - Södervik Ilona; Vilppu Henna (Springer, 2022)
Future experts of life sciences need adaptive and flexible reasoning skills in solving remarkably complex, multidisciplinary and unexpected problems, such as pandemics of severe infections, antibiotic resistance, climate change and biodiversity loss, that will require innovative ways of reasoning, and the ability to use knowledge and skills adaptively in unforeseen and adverse contexts. This requires the promotion of the so-called adaptive expertise, which is considered a separate dimension in the development of expertise that needs to be intentionally supported during higher education. Case tasks can be beneficial in this pursuit, since effective case processing and knowledge restructuring are considered to be the key concepts in expertise development. In this chapter, we synthesize the results from two of our studies, employing an eye-tracking method in which routine and non-routine text-based case tasks were used to investigate processing and problem-solving among medical actors with different levels of expertise. Our results show that the processing patterns of students and more experienced actors differed while reading case description texts. Generally, experienced actors and those students who were more successful in the case task processed the texts more quickly. Furthermore, the level and quality of basic biological knowledge seemed to be related to the success of students in problem-solving case tasks. Additionally, script activation seemed to be detectable from participants’ eye movements. These results shed light on knowledge integration and problem-solving through case processing, and show that eye tracking provides interesting insights into these areas. The results should advance the instruction of life sciences in higher education, where it is imperative to train future experts to be able to work efficiently both in predictable and especially in unpredictable circumstances.
Applying Bio-Measurements Methodologies in Science Education Research